Potential role of renewable gas in the transition of electricity and district heating systems. (January 2020) - Jensen, Ida Græsted; Wiese, Frauke; Bramstoft, Rasmus; Münster, Marie
Abstract: With the constant increase in variable renewable energy production in electricity and district heating systems, integration with the gas system is a way to provide flexibility to the overall energy system. In the sustainable transition towards a zero-emission energy system, traditional natural gas can be substituted by renewable gasses derived from anaerobic digestion or thermal gasification and hydrogen. In this paper, we present a methodology for modelling renewable gas options and limits on biomass resources across sectors in the energy optimisation model, Balmorel. Different scenarios for socio-economic pathways to emission neutral electricity and district heating systems in Denmark, Sweden, Norway and Germany, show that a renewable based energy system benefits from a certain percentage of gas as a supplement to other flexibility options like interconnectors. Especially upgraded biogas from anaerobic digestion serves as a substitute for natural gas in all scenarios. Allocating only 10% of available biomass to the electricity and district heating sector leads to full exploitation of the scarce biomass resource by boosting biogas and syngas with hydrogen. The need for renewable gasses is highest in Germany and least in Norway, where hydro-power provides flexibility in terms of storable and dispatchable electricity production. The scenarios show that a required "late sprint" from fossils to achieve a zero-emission energy system in 2050 causes (1) significant higher accumulated emissions, and (2) a system, which strongly relies on fuels, also in an emission free system, instead of stronger integration of the electricity and district heating systems through electrification as well as stronger integration of the power systems across countries through interconnectors. Highlights: Analysing the role of renewable gas in the transition to zero-emission energy systems. Simplified method for including renewable gasses in the energy systems model Balmorel. Diversity of flexibility options (transmission and gas) complement each other. Germany is more in need of renewable gas for electricity and heat than Scandinavia. Early emission reduction strengthens role of electrification instead of renewable gas.